2008
DOI: 10.1158/0008-5472.can-07-6496
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the Induction of an Angiogenesis Inhibitor, Thrombospondin-1, by 5-Fluorouracil

Abstract: 5-Fluorouracil (5-FU) is one of the most commonly used anticancer drugs in chemotherapy against various solid tumors. 5-FU dose-dependently increased the expression levels of intrinsic antiangiogenic factor thrombospondin-1 (TSP-1) in human colon carcinoma KM12C cells and human breast cancer MCF7 cells. We investigated the molecular basis for the induction of TSP-1 by 5-FU in KM12C cells. Promoter assays showed that the region with the Egr-1 binding site is critical for the induction of TSP-1 promoter activity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Therefore, 5-FU can be included in the growing list of antitumor agents such as cisplatin, ara-c or radiotherapy (Losa et al, 2003;Sanchez-Arevalo, et al, 2005;Lafarga et al, 2009), in which p38MAPK signaling pathway is a major determinant of the therapeutic effects. Previous reports indicated an activation of p38MAPK by 5-FU, but no relation to resistance was established (Elsea et al, 2008;Zhao et al, 2008). In this sense, our data in HaCaT, HCT116, HT-29, RKO, SW620 and LoVo cell lines, using pharmacological and genetic approaches, clearly demonstrate that the lack of p38MAPK activity promotes de novo and acquired resistance to 5-FU.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Therefore, 5-FU can be included in the growing list of antitumor agents such as cisplatin, ara-c or radiotherapy (Losa et al, 2003;Sanchez-Arevalo, et al, 2005;Lafarga et al, 2009), in which p38MAPK signaling pathway is a major determinant of the therapeutic effects. Previous reports indicated an activation of p38MAPK by 5-FU, but no relation to resistance was established (Elsea et al, 2008;Zhao et al, 2008). In this sense, our data in HaCaT, HCT116, HT-29, RKO, SW620 and LoVo cell lines, using pharmacological and genetic approaches, clearly demonstrate that the lack of p38MAPK activity promotes de novo and acquired resistance to 5-FU.…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, ara-c and gemcitabine are members of the same family of 5-FU (anti-metabolites), but no relationship between 5-FU resistance and p38MAPK has been reported. The only connection between 5-FU and p38MAPK is in the production of pro-inflammatory cytokines and thrombosposdin-1 in response to this drug (Elsea et al, 2008;Zhao et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Cyclophosphamide, one of the alkylating agents, that seriously damages DNA molecule was previously reported to induce TSP-1 (49). These findings together with our previous findings (23) suggest that TP is needed for the induction of Egr-1 and TSP-1 by 5-FU and the DNA damage by FdUMP caused the stress that activates p38 MAPK kinase pathway, and consequently induced Egr-1 and TSP-1 mRNA in the TPexpressing cells. Although further study is needed to elucidate whether Egr-1 and TSP-1 induction by 5-FU is implicated in the antitumor effect of 5-FU, our findings might be useful to develop new approaches for the treatment of TP-expressing tumors.…”
Section: The Effect Of LV and Tpi On The Induction Of Egr-1 And Tsp-1supporting
confidence: 75%
“…Recently, we found that 5-FU induced TSP-1 in human colon carcinoma KM12C cells (23). A transcription factor, Egr-1, was also induced by 5-FU and bound to the promoter of TSP-1, enhancing its transcription and the subsequent production of TSP-1 protein.…”
Section: The Effect Of LV and Tpi On The Induction Of Egr-1 And Tsp-1mentioning
confidence: 96%
See 1 more Smart Citation